Targeting the NLRP3 inflammasome in kidney disease: molecular mechanisms, pathogenic roles, and emerging small-molecule therapeutics - Luo, Yanfang; Long, Muyang; Wu, Xueqin; Zeng, Liuting (Frontiers in Immunology, 2025)
Inflammatory responses represent a core pathological process driving the progression of both acute and chronic kidney diseases. As a key effector of the innate immune system, the NLRP3 inflammasome is widely activated in renal resident cellsand infiltrating immune cells, positioning it as a critical nexus linking metabolic dysregulation, cellular stress, and tissue injury. Accumulating preclinical and clinical evidence in recent years demonstrates that aberrant activation of the NLRP3 inflammasome directly promotes glomerular damage, tubulointerstitial inflammation, fibrosis, and vascular dysfunction through the release of IL-1β and IL-18 and the induction of pyroptosis, thereby contributing to the pathogenesis of diverse renal disorders including acute kidney injury (AKI), diabetic kidney disease (DKD), IgA nephropathy, lupus nephritis, and chronic renal fibrosis. This review systematically delineates the multilayered regulatory mechanisms of the NLRP3 inflammasome within the renal microenvironment—including upstream activating signals, downstream effector pathways, and crosstalk with autophagy, mitochondrial dynamics, and epigenetic regulation. We particularly focus on how disease-specific triggers in kidney pathologies such as hyperglycemia, uric acid, lipotoxicity, and ischemia reperfusion instrumentalize NLRP3 to drive irreversible renal injury. Critically, we provide a comprehensive evaluation of current advances in the development of small-molecule inhibitors targeting the NLRP3 inflammasome pathway, encompassing preclinical and clinical trial data for agents that directly modulate NLRP3 protein conformation, inhibit ASC oligomerization, block caspase-1 activity, or neutralize IL-1β. We further dissect the differential therapeutic efficacy, tissue selectivity, safety margins, and emerging resistance mechanisms of these inhibitors across distinct renal disease models, while highlighting key translational challenges—including the lack of validated biomarkers, difficulties in patient stratification, and inefficient renal-targeted drug delivery. This review aims to establish a systematic theoretical framework for mechanistic research into renal inflammatory diseases and to provide a target rationale and a clinical development roadmap for the design of next-generation precision anti-inflammatory therapies, thereby accelerating the translation of NLRP3-targeted interventions from bench to bedside for patients with kidney disease.